Ecotourism Development Policy, Supporting Capacity and Development of Sustainable Tourism Facilities and Infrastructure in Raja Ampat Regency, West Papua Province - Alexander Phuk Tjilen; Willyan Sahetapy; Beatus Tambaip; Martha Betaubun (International Journal of Science and Society, 2022)
The purpose of the research is to incite the awareness of the government and stakeholders on the environmental carrying capacity of the sustainable tourism sector and the supervision of the development of facilities and infrastructure that are environmentally sound and provide added economic value to the development of local communities. Qualitative research methods are used in data collection by conducting direct visits to research sites, direct interviews with the tourism office of Raja Ampat Regency, tourism management communities, tour guides and homestay managers with research locations on Misool Island, Salawati, Batanta, and Waigeo Raja Regency. Ampat. The study results explain that a marine tourism location is vulnerable to coral and environmental damage caused by overexploitation; it requires strict supervision and supervision from all parties as well as binding regulations so that the carrying capacity of Raja Ampat is well maintained and sustainable. The construction of facilities and infrastructure must be planned and supervised to achieve green development in determining tourist locations, homestay building locations, development processes and environmentally friendly materials. Communities need to be empowered with funding assistance and operational management training for marine tourism and homestay management, using local wisdom in maintaining ecotourism sustainability